EFFECT OF CHANGING ASPECT RATIO, EXPANSION RATIO AND OVALITY PARAMETER ON EXPANSION CHAMBER FOR THE PERFORMANCE OF SOUND TRANSMISSION LOSS - Amit Kumar Gupta, Rahul Suman (International Journal of Research Science and Management, 2015)
This paper shows the measurement of the Acoustic Transmission Loss of different expansion chamber which is shown by using Finite element Analysis (FEM). For these purpose the evaluation of transmission loss of different cross-sections by keeping constant volume of expansion chamber is explained. To observe the effect of transmission loss of Expansion chamber with changing the L/D ratio of the circular cross-section, effect of transmission loss of expansion chamber with changing the expansion ratio for the circular cross-section and to observe the effect of transmission loss of Expansion chamber with changing ovality parameter for the elliptical cross-sections by designing in FEA Acoustic Module.